Revision of the genus Caledonica Chaudoir, 1860 (Coleoptera: Cicindelidae). - Kudrna, Arnošt (Jihočeská univerzita, 2014)
New Caledonian tiger beetle genus Caledonica was revised. Study was based on specimens in museum and author´s private collections and also on living specimens directly in their biotopes during three field research trips. Detailed description or redescription of all taxa is given supplemented with data on behaviour observations in their biotopes and all descriptions are fully illustrated.
Revision of the genus Caledonica Chaudoir, 1860 (Coleoptera: Cicindelidae).
Keywords: New Caledonia; Caledonica; description and redescription; new taxon; behavior.; New Caledonia; Caledonica; description and redescription; new taxon; behavior.